2010
DOI: 10.1038/leu.2010.113
|View full text |Cite
|
Sign up to set email alerts
|

IDH1 and IDH2 mutation studies in 1473 patients with chronic-, fibrotic- or blast-phase essential thrombocythemia, polycythemia vera or myelofibrosis

Abstract: In a multi-institutional collaborative project, 1473 patients with myeloproliferative neoplasms (MPN) were screened for isocitrate dehydrogenase 1 (IDH1)/IDH2 mutations: 594 essential thrombocythemia (ET), 421 polycythemia vera (PV), 312 primary myelofibrosis (PMF), 95 post-PV/ET MF and 51 blast-phase MPN. A total of 38 IDH mutations (18 IDH1-R132, 19 IDH2-R140 and 1 IDH2-R172) were detected: 5 (0.8%) ET, 8 (1.9%) PV, 13 (4.2%) PMF, 1 (1%) post-PV/ET MF and 11 (21.6%) blast-phase MPN (P<0.01). Mutant IDH was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
222
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(230 citation statements)
references
References 44 publications
6
222
1
1
Order By: Relevance
“…[26][27][28][29] IDH1 and IDH2 mutations were analyzed by direct sequencing and/or high-resolution melting assay. 30 Unfavorable karyotype designation 31 and International Prognostic Scoring System (IPSS), 32 DIPSS, 33 and DIPSSplus 21 21 Leukemic transformation risk was considered high in the presence of unfavorable karyotype or platelet count less than 100 ϫ 10 9 /L or low in the absence of both of these risk factors. 21 All statistical analyses considered clinical and laboratory parameters obtained at time of first referral to Mayo Clinic.…”
Section: Methodsmentioning
confidence: 99%
“…[26][27][28][29] IDH1 and IDH2 mutations were analyzed by direct sequencing and/or high-resolution melting assay. 30 Unfavorable karyotype designation 31 and International Prognostic Scoring System (IPSS), 32 DIPSS, 33 and DIPSSplus 21 21 Leukemic transformation risk was considered high in the presence of unfavorable karyotype or platelet count less than 100 ϫ 10 9 /L or low in the absence of both of these risk factors. 21 All statistical analyses considered clinical and laboratory parameters obtained at time of first referral to Mayo Clinic.…”
Section: Methodsmentioning
confidence: 99%
“…IDH mutations occur at low frequencies (3.6-5%) in myelodysplastic syndrome, 3,4 and in chronic-phase myeloproliferative neoplasm (about 1.8%), 5,6 but obviously increased as these diseases progress to AML (7.5-21%), [3][4][5][6] indicating a role of IDH mutations in leukemogenesis. In AML, IDH2 mutations occur more frequently than IDH1 mutations, with frequencies of 11 vs 6% in patients younger than 60 years, 7 15.4 vs 7.7% in total patients, 8 and 19 vs 14% in adults with normal karyotype.…”
Section: Introductionmentioning
confidence: 99%
“…2,29,30 A recent multi-institutional study in 1473 MPN patients has reported IDH mutation frequencies of 25% for blast phase polycytemia vera and for blast phase primary myelofibrosis, as against 1% for essential thrombocytemia, 2% for polycytemia vera and 4% for primary myelofibrosis in CP. 4 Similarly, IDH mutations have been detected in up to 15% of secondary AML evolved from an MDSFas against 3.6-5% of early stage MDS. 3,31 This striking association of IDH mutations with transformed/progressive disease in the context of MPN/MDS has further been strengthened by the results of a very recent study comparing mutation frequencies within a relatively well-defined, genetically homogeneous patient population, that is, between low-risk MDS and high-risk MDS/AML cases with isolated deletion of chromosome 5q (0 and 22%, respectively).…”
mentioning
confidence: 98%
“…We read with interest a series of manuscripts, [1][2][3][4][5][6] reporting somatic mutations of the isocitrate dehydrogenase 1 and 2 enzyme isoforms (IDH1, IDH2) in patients with de novo acute myeloid leukemia (AML), in patients with chronic and blast phase Philadelphia chromosome-negative (Ph-) myeloproliferative neoplasms (MPNs) and in patients with early and accelerated phase myelodysplastic syndromes (MDSs).…”
mentioning
confidence: 99%
See 1 more Smart Citation